ANALISIS KUALITAS PRODUK, HARGA, ONLINE CUSTOMER REVIEW DAN ONLINE CUSTOMER RATING TERHADAP MINAT BELI SKINCARE SKINTIFIC SHOPEE ONLINE SHOP - Ariani, Ade Mita; Nasution, Siti Lam’ah; Hendry, Raja Saul Marto (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to analyze the analysis of product quality, price using online customer reviews and online customer ratings on interest in buying Skintific Skincare Shopee Online Shop (Case Study: Semester VII Management Students at Labuhanbatu University), the influence of product quality on interest in buying Skintific Skincare Shopee Online Shop, From the research obtained, the magnitude of the influence of price on interest in buying Skincare Skintific Shop Online Shop shows that the t-count value is 2.171 and the sig value. 0.032 < 0.05. Thus, the Product Quality variable (X1) has a partial effect on Purchase Interest (Y), from the research it was found that the Influence of Price on Purchase Interest of the Skintific Shopee Online Shop t test showed that the t-count value was 2.949 and the sig value. 0.004< 0.05. Thus, the Price variable (X2) has a partial effect on Purchase Intention (Y), the Influence of Online Customer Reviews on Purchase Intention to Buy Skincare Skintific Shopee Online with the t test that the t value is 2.536 and the sig value. 0.013 < 0.05, thus the Online Customer Review Variable (X3) has a partial effect on the Purchase Interest in Skincare Skintific Shopee Online Shop (Y). The influence of online customer ratings on interest in purchasing Skincare Skintific Shop Online Shop t test shows that the t value is 1.217 and the sig value. 0.226 > 0.05. This means that the Online Customer Rating (X4) variable has no partial effect on Purchase Interest (Y) and the F test in this research is the sig value. 0.000 < 0.05, thus the variables Product Quality, Price, Online Customer Review and Online Customer Rating have a simultaneous influence on Interest in Buying Skintific Shopee Online Shop. The Adjusted R Square value is 0.309, meaning that the independent variables together have an influence on the attachment variable of 30.9 %. while the remaining 69.1% was influenced by other factors not included in this study.